Bioinformatics and Molecular Docking Study of Amentoflavone and 3,8-Biapigenin as Inhibitors on Cervical Cancer Proteins - Ningrum, Dhecella Winy Cintya; Kusumaningtyas, Triana Arum; Febriansah, Rifki; Juniananda, Melisa; Tasminatun, Sri; Krisridwany, Annisa (Indonesian Journal of Cancer Chemoprevention, 2023)
Cervical cancer maintains its second-place ranking for Indonesia's highest number of cancer cases. In 2021, there were 36,633 cases of cervical cancer in Indonesia, with a rising death rate. Commonly, chemotherapy is used to treat cervical cancer and can improve the survival chances of patients, but these therapies imply increased toxicity. Biflavonoid group compounds like amentoflavone and 3,8-Biapigenin have the potential to act as anticancer agents by modulating multiple signaling pathways. This study aims to determine the cervical anticancer potential of amentoflavone and 3,8-Biapigenin based on in silico study. Prediction of anticancer activity in silico using Prediction of Activity Spectra for Active Substances (PASS) online, followed by target protein tracing using STITCH-STRING, then receptor analysis test using Ramachandran plot. A molecular docking test was conducted to determine the binding affinity of the compound with the receptor. Based on the online PASS, the compounds as thought to have low cervical anticancer potential if tested on a laboratory scale. STAT3, EP300, CYP1A1, and AKR1C1 proteins used in this study have met the requirements of a suitable receptor for molecular docking test. The best binding affinity was obtained at the interaction of amentoflavone and STAT3 with a better docking score (-9.3 kcal/mol) than doxorubicin (-7.1 kcal/mol). Overall, the results suggest biflavonoid compounds have the potential to be developed as a chemopreventive agent for cervical cancer.Keywords: bioinformatics, molecular docking, amentoflavone, 3,8-Biapigenin, cervical cancer protein.